A Systematic Review of the Parenting, Feeding, Behavior, Family, and Nutrition for Children with Avoidant Restrictive Food Intake Disorder (ARFID) - Yoyok Bekti Prasetyo; Salahudin; Nurlailatul Masruroh; Anggraini Dwi Kurnia; Nur Melliza (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: Parenting is an essential factor in causing ARFID. A good understanding of parenting, feeding,behavior, family, and nutrition can provide better care. The present study aimed to investigate parenting,feeding, action, family, and food in children with ARFID.Review: Relevant database for systematic search of ARFID studies.Result: The review results found that there were five important themes in the case of children with ARFID.The five themes include parenting, feeding, behavior, family, and nutrition. There is a relatively strongrelationship, namely the relationship between parenting-feeding, parenting-behavior, parenting-family,parenting-nutritional sequentially (r = 0.72; r = 0.66; r = 0.59; r = 0.59 ).Conclusion: Important factors that must be understood by families and the health care team in providingcare for ARFID children include: parenting, feeding, behavior, family, and nutrition. A good understandingof these factors can be used as guidelines for providing nursing care in children with ARFID.